Hastings Alumni and Fresno County Bar Association Joint Luncheon with California Supreme Court Justice Wiley Manuel - Watkins, Howard::::::::: (1979)
Howard Watkins, Baxter Richardson, Hon. Wiley Manuel, David St. Louis, Hastings Alumni Director Libby Strobe head table at Fresno Hilton Hotel